Evaluation of the Effect of Eslicarbazepine Acetate on the Pharmacokinetics of Perampanel in Rats by Isotope-Dilution-UHPLC-MS/MS - Liu P; An J; Wu H (Dove Medical Press, 2022)
Ping Liu,1,2 Jing An,2 Huizhen Wu1,2 1Graduate School of Hebei Medical University, Shijiazhuang, People's Republic of China; 2National Clinical Drug Monitoring Center, Department of Pharmacy, Hebei General Hospital, Shijiazhuang, People's Republic of ChinaCorrespondence: Huizhen Wu, National Clinical Drug Monitoring Center, Department of Pharmacy, Hebei General Hospital, No. 348, West Heping Road, Shijiazhuang, 050051, People's Republic of China, Email 13582005982@163.comPurpose: The present study aimed to establish and validate an isotope-dilution-UHPLC-MS/MS method for the determination of perampanel (PER) concentration and investigate the effect of eslicarbazepine acetate (ESL) on the pharmacokinetics of PER in rats.Methods: The rats were randomly divided into the control (0.5% CMC-Na) and experimental groups (ESL, 72 mg/kg), with six rats in each group. A single dose of PER (1 mg/kg) was administered after a week of repetitive 0.5% CMC-Na or ESL dosing (72 mg/kg); then, plasma samples were collected. Perampanel-d5 (PER-d5) was used as the internal standard (IS), liquid-liquid extraction of plasma samples was carried out using ethyl acetate, and chromatographic separation was carried out on a Titank C18 column (2.1 mm × 50 mm, 3.0 μm) using a gradient mobile phase consisting of 0.1% formic acid and acetonitrile at a flow rate of 0.3 mL/min.Results: PER had good linearity (0.3- 600 ng/mL, r > 0.999), and the accuracy, precision, recovery rate, and matrix effects (ME) met the Food and Drug Administration (FDA) guidelines. Compared to the control group, the area under the curve AUC0→t, AUC0→∞, and Cmax of PER in the experimental group decreased by 30.28%, 30.34%, and 46.94%, respectively, and CL increased by 32.08%.Conclusion: ESL could induce the metabolism of PER in rats and decreases plasma exposure to PER. Thus, the concomitant treatment with ESL may require a high dose of PER to achieve the same efficacy.Keywords: perampanel, eslicarbazepine acetate, pharmacokinetics, UHPLC-MS/MS, drug-drug interactions, Sprague-Dawley rats